TECHNICAL ANALYSIS OF THE MINE DEWATERING SYSTEM DESIGN BASED ON EXTREME RAINFALL FOR ACCELERATING IN-PIT DUMP AT PIT ABC, PT XYZ - Dewa Yasthy, Rifky
The coal mining company, PT XYZ, requires acceleration of the in-pit dump at pit ABC, located in the southern zone of the ABC sump area at an elevation of 24 meters above sea level. To support this need, an analysis of a mine dewatering system plan appropriate to the field conditions is necessary. One option to support this need is the construction of an open channel in the low wall of pit ABC to reduce inflow and the implementation of a pumping system as an outflow function to optimize the acceleration of the in-pit dump. The dewatering system analysis is conducted through the evaluation of three schemes (A, B, and C) that vary the position of the open channel at elevations of 120, 103, and 94 meters above sea level. The criteria for selecting the best scheme will be evaluated based on the volume of water accumulated in the sump, the volume of water diverted by the open channel, the volume cut of the open channel, and the drainage time in the sump. The data used include secondary data, such as daily rainfall data for the period 2013–2022, the pit ABC situation map for 2023, and information on the drainage system network. The analysis results show that the volume of water accumulated in the sump of pit ABC for a 2-year return period under existing conditions reaches 54,290 m³ per day, requiring a drainage time of 3 days and 5 hours using one pump unit with a capacity of 1,050 m³ per hour. For optimization schemes A, B, and C, the volumes of water accumulated in the sump of pit ABC are 29,612.8 m³, 25,225.7 m³, and 22,483.8 m³, with drainage times of 1 day 7 hours, 1 day 1 hour, and 21 hours, respectively. The volumes of diverted water are 24,667.3 m³, 29,612.8 m³, and 31,806.3 m³, and the volumes cut by the open channel are 3,295.9 m³, 3,387.5 m³, and 3,508.6 m³. Considering the drainage times, Optimization Scheme C is recommended due to its shortest drainage time, which aligns with the need to accelerate the in-pit dump at pit ABC.